Dijital Boyamanın Evriminde Sanal Gerçeklik Boyutu. - KARA, Murat (Journal of Social Sciences Research / Sosyal Bilimler Araştırmaları Dergisi, 2020)
People who have been trying to reach the reality by questioning it throughout the history of art, have tried to use the high technology that each period has in its own conditions. While the coexistence of technology with art has enabled the development of various techniques, it has also led artists/designers to new pursuits. The process of digitalization, which began with the invention of the computer, brought alternatives to forms of expression in art production and paved the way for artistic production techniques adapted to the emerging new media environment. It became possible to create the traditional painting works in digital media by using computer aided softwares and hardwares. The development of graphic softwares and hardwares, which previously could only allow simplest level of drawing and painting, has made it possible to create 3D images on a two-dimensional plane. A fterwards, digital painting t echniques, which keep pace w ith t he developing t echnological opportunities, have been able to be applied in 3D or virtual reality environment. T here is no doubt that, it is necessary to address the history of digital painting techniques that have reached this level. Therefore, in this study, a general evaluation is made on perceptions of reality in the field of art and design, technical information is given about the development process of digital painting techniques, which has almost reached reality, and predictions about their future use are underlined.